Event Ubud Writers & Readers Festival Sebagai Promosi Destinasi Ubud - Ni Made Sri Purnami; I Nyoman Darma Putra; Putu Sucita Yanthy (JURNAL MASTER PARIWISATA, 2022)
The event industry is growing rapidly and has become one of the attractions of a destination. Since the early 2000s, Ubud destination has become known with the presence of various festival events, such as the Ubud Writers & Readers Festival (UWRF), Bali Spirit Festival, Ubud Village Jazz Festival and Ubud Food Festival. The events aim to promote Ubud as a tourist destination. Ubud known as a cultural tourist destination that has a beautiful landscape, and now event can be additional value for the destination popularity. This article discusses the role of Ubud Writers and Readers Festival in helping to strengthen dimension of Ubud images as cultural destination. By applying qualitative research method, the research collected data by interview, observation, library research and examining UWRF archive. The research showed that apart showing dynamic program of literary event involving famous and emerging authors, the UWRF also promote Ubud as tourist destination. This can be seen from the steady increase of participants who come to Ubud not only to participate in the festival but also as visitors. In addition, the success of UWRF increases the popularity of Ubud in particular and Bali in general. Keywords: events, promotions, cultural tourism, Ubud tourism destination, Ubud writers & readers festival